2022
DOI: 10.1111/jopr.13486
|View full text |Cite
|
Sign up to set email alerts
|

CAD‐CAM Fabricated Denture Base Resins: In Vitro Investigation of the Minimum Acceptable Denture Base Thickness

Abstract: Purpose To investigate the influence of reducing material thickness on flexural properties of computer‐aided design and computer‐aided manufacturing (CAD‐CAM) denture base resins. Materials and methods Four CAD‐CAM denture base acrylic resin materials were selected; two were made via the subtractive method (AvaDent and IvoCad) and two were made with the additive method (FormLabs and NextDent). One heat‐polymerized denture base material was used as a control. Specimens were fabricated with varying thicknesses (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 40 publications
1
5
0
1
Order By: Relevance
“…Superior mechanical properties of CAD‐CAM denture base resins when compared with those conventionally fabricated have been previously reported 10 . In addition, previous studies on the FS of milled and additively manufactured denture base resins reported higher FS for milled groups, which is in line with the present study results 19–21 . The minimum FS required for denture base resins has been described as 65 MPa 22 .…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Superior mechanical properties of CAD‐CAM denture base resins when compared with those conventionally fabricated have been previously reported 10 . In addition, previous studies on the FS of milled and additively manufactured denture base resins reported higher FS for milled groups, which is in line with the present study results 19–21 . The minimum FS required for denture base resins has been described as 65 MPa 22 .…”
Section: Discussionsupporting
confidence: 92%
“…10 In addition, previous studies on the FS of milled and additively manufactured denture base resins reported higher FS for milled groups, which is in line with the present study results. [19][20][21] The minimum FS required for denture base resins has been described as 65 MPa. 22 This threshold value was reached by both milled groups, but not by the additively manufactured specimens, regardless of the condition.…”
Section: Discussionmentioning
confidence: 99%
“…There is no doubt that milling flat surface specimens is simple and produces a smoother surface compared to 3D printing if proper machine settings were selected. 15 Another issue in the 3D printing process that could be source of roughness is the possibility of partially cured particle formation especially if adequate post-curing is not achieved. These particles may dislodge and form minute porosities.…”
Section: Discussionmentioning
confidence: 99%
“…Digital technologies provide the advantage of rapid denture manufacturing and fewer stages in the workflow, which can lessen the likelihood of errors. 9,10,15 While milling is commonly used to make digital dentures, 3D printing denture bases has several benefits. It is less expensive, does not require the use of rotary tools, produces minimal wastage, and has the capability to generate several objects at the same time.…”
Section: Introductionmentioning
confidence: 99%
“…Podczas frezowania dochodzi do strat materiału, w przeciwieństwie do druku 3D, który jest procesem bardziej wydajnym, pozwalającym na pozyskiwanie większych obiektów o dowolnym kształcie. 1,12,19,20 Szeroko opisywane w piśmiennictwie jest wykorzystanie metod cyfrowych do projektowania i wytwarzania stałych uzupełnień protetycznych, komponentów implantologicznych, takich jak: szablony, indywidualne łączniki czy elementy precyzyjne, oraz coraz częściej również uzupełnień ruchomych. 1,21,22 Po resekcji tkanek w zakresie podniebienia wskazane jest jak najszybsze uzupełnienie powstałego ubytku w celu przywrócenia funkcji i poprawy jakości życia.…”
Section: Wykorzystanie Technologii Cyfrowych W Rehabilitacji Protetyc...unclassified